Antimicrobial properties of nanobiomaterials and the mechanism - Chan, Yen (2016)
Various physical and chemical methods have been used extensively on an industrial scale to produce nanobiomaterials. The use of toxic chemicals and their stability are of vital concern. Toxic chemicals are used on the surface of nanobiomaterials and as non-polar solvents during their synthesis. However, the use of toxic chemicals is not suitable in the clinical field. Synthesizing these nanobiomaterials using a green, bottom-up approach, which is regarded as safe, eco-friendly, cost-effective and sustainable, is the way forward. As the demand for these materials increases, it is crucial to determine a cost-effective, large-scale and eco-friendly green method to synthesize them. Even though there are many green synthesis methods for the production of nanobiomaterials, there has been less work reported on antimicrobial properties of nanobiomaterials and their reaction mechanism. This chapter highlights the history of antimicrobial agents, nanobiomaterials as antimicrobial agents and their reaction mechanism. The use of nanomaterials in food packaging, water purification, and disinfection are also discussed.